Total thyroidectomy is superior for initial treatment of thyroid cancer. Issue 5 (5th August 2020) - Han, Lin; Li, Wenlei; Li, Yingxue; Wen, Wenjuan; Yao, Yumin; Wang, Yongkun
Abstract: Purpose: The incidence of thyroid cancer has increased annually, and has a heavy psychological and economic burden on the society and individuals. Based on thyroid cancer data from patients treated in Liaocheng People's Hospital in 2017, with Chinese national and regional characteristics, in this study we addressed the controversy of which initial thyroid surgical mode, lobectomy, or total thyroidectomy is the most effective. Patients and methods: Clinical and pathological data from 552 patients with thyroid cancer, who were initially diagnosed and treated surgically, were collected from the Department of Thyroid Surgery. Among them, 40 patients underwent endoscopic surgery, with resection, including lobectomy + central lymph node dissection of the affected lobe, while 512 cases underwent total thyroidectomy + central lymph node dissection. Results: The metastasis rate for all patients was 59.42%, with lymph node metastasis of papillary thyroid microcarcinoma of 46.92%; however, for patients with tumors >2 cm, the proportion developing metastasis was increased to 77.53%. Conclusion: In thyroid cancer, rates of neck lymph node metastasis are high, particularly among patients with risk factors for poor prognosis. Our data suggest that initial treatment should comprise at least total thyroidectomy + central lymph node dissection in China, at least in tumors larger than 1 cm, to avoid the risks associated with secondary surgery and effects on patient quality of life.